2017
DOI: 10.1002/ejsp.2336
|View full text |Cite
|
Sign up to set email alerts
|

The evil eye: Eye gaze and competitiveness in social decision making

Abstract: We demonstrate that a person's eye gaze and his/her competitiveness are closely intertwined in social decision making. In an exploratory examination of this relationship, Study 1 uses field data from a high‐stakes TV game show to demonstrate that the frequency by which contestants gaze at their opponent's eyes predicts their defection in a variant on the prisoner's dilemma. Studies 2 and 3 use experiments to examine the underlying causality and demonstrate that the relationship between gazing and competitive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In other words, teachers' gaze towards students in the classroom is likely to send communing signals to students and teachers' communicative gaze towards their students functions more in terms of social affiliation, more associated with friendliness, rather than messages of threat and dominance. Suggestions that teacher gaze towards students is linked with dominance, threat and aggression (e.g., Ellsworth 1975;Giacomantonio et al 2018;Kleinke 1986) should therefore be tempered with considerations of the context in which eye contact occurs (Wu et al 2014). Moreover, it appears that teachers capitalise on the natural pedagogy (Csibra and Gergely 2009) and the universal impact of direct gaze , as they invite and encourage students to receive information by signalling communicative intent (Csibra 2010) via their communicative gaze.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, teachers' gaze towards students in the classroom is likely to send communing signals to students and teachers' communicative gaze towards their students functions more in terms of social affiliation, more associated with friendliness, rather than messages of threat and dominance. Suggestions that teacher gaze towards students is linked with dominance, threat and aggression (e.g., Ellsworth 1975;Giacomantonio et al 2018;Kleinke 1986) should therefore be tempered with considerations of the context in which eye contact occurs (Wu et al 2014). Moreover, it appears that teachers capitalise on the natural pedagogy (Csibra and Gergely 2009) and the universal impact of direct gaze , as they invite and encourage students to receive information by signalling communicative intent (Csibra 2010) via their communicative gaze.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was concluded that the right hemisphere was associated primarily with perception of upper facial emotions. The perceptual bias to lower facial expressions under the no attend condition was attributed to three possibilities: (1) subjects normally attend to the lower face to enhance verbal comprehension, especially in noisy environments ("McGurk effect") [205][206][207], (2) due to cultural norms, subjects focus their visual attention to the lower face in order to avoid direct eye contact which is perceived as being aggressive and threatening in humans ("evil eye") and other animals, unless there is mutual affiliation [208][209][210][211], and (3) the left-hemisphere is more involved with foreground (conscious) processing of visual information whereas the right hemisphere is more involved with background (subconscious) processing of visual information [212,213] that can be brought to the foreground by altering an individual's attentional bias. This conscious-subconscious dichotomy also appears to extend to the perception and processing of emotional information conveyed by facial expressions and affective prosody during social interactions [214,215] but not for intense emotional experiences that may bring the right hemisphere's perceptions to the foreground [1].…”
Section: Are There Other Lines Of Research That Support the Emotion-type Hypothesis?mentioning
confidence: 99%
“…For example, staring that appears unnaturally fixed, or too much eye-directed gaze, could certainly tip perception of the leader from authentic to artificial, or even provocative (e.g. Giacomantonio, Jordan, Federico, van den Assem, & van Dolder, 2018). Indeed, it is well-known that certain factors can be beneficial to overall leader effectivity, and yet turn detrimental when overdone (e.g.…”
Section: Future Research Directions and Limitationsmentioning
confidence: 99%